Soil moisture induced yield variability in major crops of Karnataka - SHIVARAMU, H S; MANJUNATHA, M H; HUGGI, LINGARAJ; BAL, SANTANU KUMAR; KUMAR, P VIJAYA; PADMASHRI, H S; SOUMYA, D V; NAGESHA, L; MOHANTY, M (The Indian Journal of Agricultural Sciences, 2022)
South interior Karnataka, being a major rainfed zone contributing to production of pigeonpea, finger millet, groundnut, etc., suffers from severe yield instability due to dependency on rainfall. As the distribution of rainfall (spatial and temporal) is erratic, droughts are becoming a common phenomenon and adversely affecting regional crop production by influencing soil moisture availability. Regression studies on per cent available soil moisture (PASM) and yield were conducted based on long-term field observations in 2014–19 on soil moisture and crop yields in finger millet, pigeonpea and groundnut at UAS-GKVK, Bengaluru. The outcomes indicated large yield variability due to minor soil moisture differences. In finger millet, at 58 PASM, 50% (1500 kg/ha) of normal yield was obtained and at 40 PASM, only 25% of normal yield was obtained. In pigeonpea, the crop yield recorded at 25 PASM was 8–18% (202–347 kg/ha) of the normal yield. In groundnut 50 PASM gave 41% of normal yield. The outcome indicated different soil moisture requirement for different crops, stressed the need for amending existing non-crop specific PASM ranges for drought declaration. Amendments were brought in by considering different PASM levels in these three crops finger millet: 20–40 as severe, 40–60 as moderate, >60 as no drought; in pigeonpea, 25–30 as severe, 30–60 as moderate, >60 as no drought; in groundnut, 35–50 as severe, 50–70 PASM as moderate, >70 as no drought. Since the practicality of the study was proven, the amendments were given in the drought manual published by ministry of farmers’ welfare.